Helminth parasites of the African lizard Agama agama (Squamata: Agamidae), in Lagos, Nigeria - Adeoye, G.O. (2007)
Agama agama, the agamid rainbow lizard, has been reported to serve as transport and reservoir host to several protozoan and helminth parasites. We randomly sampled 310 specimens between May and July, 2005, at Oyingbo, Lagos, Nigeria (6°34'60'' N-3°19'59'' E and 6°34'60'' N-3°19'59'' E).They harboured four species of nematodes: Strongyluris brevicaudata, Parapharyngodon awokoyai, Capillaria sp. and Oxyuris sp.; one of Cestoda, Oochoristica agamae; one of Trematoda, Mesocoelium monas; and one of Pentastomida, Raillietiella sp. Strongyluris brevicaudata had the highest prevalence of infection (82.3 %), followed by P. awokoyai (74.5 %), Raillietiella (10.3 %), Capillaria sp. (8.4 %) and O. agamae (7.4 %). M. monas and Oxyuris sp. had low prevalences: 1.61 % each. Raillietiella sp. and Capillaria sp. can cause localized inflammation and intestinal infections in humans. The prevalence of infection was higher in larger adult lizards. Prevalence in males was 97.6 % (94.1 % in females). In four of the helminth species, intensity of infection was higher in male lizards. Parasite intensity was highest in the rectum, followed by the intestine (p < 0.05). Infection intensity was, to a large extent, dependent on the type of parasite, and age of lizard. During May, P. awokoyai had its highest mean intensities and prevalence. The prevalence and mean intensity of helminthes varied with the month of collection (both p < 0.05). For the three months studied, prevalence and mean intensity of S. brevicaudata were highest in June (July for the other species).